Secondhand smoke levels in Scottish pubs: the effect of smoke-free legislation. Issue 2 (30th March 2007) - Semple, Sean; Creely, Karen S; Naji, Audrey; Miller, Brian G; Ayres, Jon G
Abstract : Objective: To compare levels of particulate matter, as a marker of secondhand smoke (SHS) levels, in pubs before and 2 months after the implementation of Scottish legislation to prohibit smoking in substantially enclosed public places. Design: Comparison of SHS levels before and after the legislation in a random selection of 41 pubs in 2 Scottish cities. Methods: Fine particulate matter <2.5 μm in diameter (PM2.5 ) was measured discreetly for 30 min in each bar on 1 or 2 visits in the 8 weeks preceding the starting date of the Smoking, Health and Social Care (Scotland) Act 2005 and then again 2 months after the ban. Repeat visits were undertaken on the same day of the week and at approximately the same time of the day. Results: PM2.5 levels before the introduction of the legislation averaged 246 μg/m 3 (range 8–902 μg/m 3 ). The average level reduced to 20 μg/m 3 (range 6–104 μg/m 3 ) in the period after the ban. Levels of SHS were reduced in all 53 post-ban visits, with the average reduction being 86% (range 12–99%). PM2.5 concentrations in most pubs post-ban were comparable to the outside ambient air PM2.5 level. Conclusions: This study has produced the largest dataset of pre- and post-ban SHS levels in pubs of all worldwide smoke-free legislations introduced to date. Our results show that compliance with the Smoking, Health and Social Care (Scotland) Act 2005 has been high and this has led to a marked reduction in SHS concentrations in Scottish pubs, thereby reducing both the occupational exposure of workers in the hospitality sector and that of non-smoking patrons.